2002
DOI: 10.1590/s0004-282x2002000200027
|View full text |Cite
|
Sign up to set email alerts
|

Sequela comportamental pós-traumatismo craniano: o homem que perdeu o charme

Abstract: RESUMO -É apresentado caso de traumatismo craniencefálico com sintomas de síndrome disexecutiva ou do lobo frontal: apatia, apragmatismo e perda de habilidades prévias, mais evidentes na interação social -em especial com o sexo oposto -que resultou em prejuízo do charme que lhe era característico. São comentados os resultados do exame neuropsicológico, que evidenciou dismnésia de recuperação com reconhecimento normal, diminuição da destreza motora e da flexibilidade cognitiva, na presença de inteligência norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
12

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 2 publications
2
2
0
12
Order By: Relevance
“…Some of the difficulties might be due to sustained attention deficits, EFs deficits, and primary memory deficit -this last deficit was not found among the other cases. Mattos et al 16 documented a case of behavioral changes after TBI similar to this case, in an individual with no history of psychiatric disorder or EFs deficits who became mildly apathetic. The case reported by Mattos et al 16 revealed neuropsychological impairments others than only EFs deficits, such as long-term memory loss and visual-motor dexterity.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Some of the difficulties might be due to sustained attention deficits, EFs deficits, and primary memory deficit -this last deficit was not found among the other cases. Mattos et al 16 documented a case of behavioral changes after TBI similar to this case, in an individual with no history of psychiatric disorder or EFs deficits who became mildly apathetic. The case reported by Mattos et al 16 revealed neuropsychological impairments others than only EFs deficits, such as long-term memory loss and visual-motor dexterity.…”
Section: Discussionsupporting
confidence: 53%
“…Mattos et al 16 documented a case of behavioral changes after TBI similar to this case, in an individual with no history of psychiatric disorder or EFs deficits who became mildly apathetic. The case reported by Mattos et al 16 revealed neuropsychological impairments others than only EFs deficits, such as long-term memory loss and visual-motor dexterity. Lack of persistence was described in the case of Mattos; CM case is also characterized by "hot" EFs deficits, such as pattern of choices based on immediate reward (see IGT), which indicates cognitive impulsivity, despite having also some apathy.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the last 5 years, some studies in Brazil began to employ the Stroop paradigm to assess atentional selectivity in adults 26,27 and children 28,29 with different pathologies as, for example, ADhD and head trauma injury. Also, in one study, normative data were collected for pre-adolescents between 12 and 14 years of age 30 .…”
mentioning
confidence: 99%
“…Além disso, não mostra habilidade de monitorar seu próprio comportamento de acordo com a sua idade e em poucos períodos toma alguma iniciativa. Portanto, concordando com Mattos, Saboya, & Araújo (2002), essa criança apresenta comprometimento sócio-ocupacional que é compatível com uma alteração de funções frontais. Rodríguez, Albuquerque & Arenas (1999) apontam que o quadro clí-nico de um indivíduo com alterações no lobo frontal pode comportar alterações das funções cognitivas, do pensamento e da sexualidade, segundo as classificações internacionais.…”
Section: A Condição Neurológicaunclassified